Patient's Peak Skin Dose evaluation using Gafchromic films in interventional cardiology procedures and its correlation with other dose indicators. (September 2018) - Pasquino, M.; Cutaia, C.; Poli, M.; Valero, C.; Peroni, G.; De Benedictis, M.; Petrucci, E.; Stasi, M.
Highlights: Modern angiographic systems register Dose Area Product at the end of the procedures. Patient's Peak Skin Dose can be measured by means of Gafchromic film. A correlation between DAP and PSD can be found. Patients exceeding a PSD threshold are identified. A follow-up program to prevent skin deterministic effect can be easily implemented. Abstract: Objective: Number and complexity of interventional cardiology procedures have increased during last years and can result in patient skin dose high enough to cause deterministic skin effects. The aim of the work is to investigate the correlation between Peak Skin Dose (PSD) and the dosimetric indicators directly registered by the radiological equipment and provide the physicians a tool to identify patients at risk of deterministic effects and include them into a follow-up program. Methods: PSD was measured in vivo using radiochromic Gafchromic XR-RV3 films, properly calibrated. DAP, Cumulative Dose at the interventional reference point (CD) and exposure time of each procedure were retrieved from the Radiation Dose Structured Reports created by an Allura Clarity Xper FD20 angiographic system. Linear correlation between PSD and both DAP and CD was investigated. Results: 42 interventional cardiology procedures (16 CA and 26 PTCA) were involved in the study. The dosimetric indicators values for PTCA are generally higher than those for CA, due to the different levels of procedure complexity. Mean PSD values were (103 ± 64) and (526 ± 436) mGy for CA and PTCA procedures. For CA, we found strong correlation both between PSD and DAP (r = 0.753) and PSD and CD (r = 0.782). For PTCA, good correlation both for DAP (r = 0.648) and CD (r = 0.649) was found. Conclusions: DAP and CD show strong correlation with PSD measured with Gafchromic films during interventional procedures. The proposed method allows the physician to estimate patient's PSD from the dosimetric indicators that the radiological equipment display and record at the end of the procedure.